Análisis fisicoquímico y sensorial de queso fresco con reemplazo de grasa por lípidos de aguacate (Persea americana Mill V. Hass) (2019)
A current trend in cheese making is to substitute milk fat for its high content of saturated fatty acids (SFA), with lipids of vegetable origin and avocado for its high content of unsaturated fatty acids (AGI) mainly oleic acid and phytosterols. (campesterol, β-Sitosterol), has been valued by promoting healthy benefits to the consumer. The objective of this study was to evaluate with judges the liking or dislike of the cheeses made with fat replacement and to analyze the texture profile (TPA). The cheeses elaborated with three levels of avocado pulp were analyzed by means of a 5point hedonic test with 109 judges and the analysis of texture profile with texturometer model TA-XT2i. The T4 with the 18% added pulp was the one liked most according to the DMS test when determining the acceptance of the cheeses, although no differences were found between the T3 and the T4; the T2 was the least liked product. In the texture profile analysis, significant differences were found with respect to the control; the avocado pulp as a substitute for fat in the cheeses generated low values in the textural parameters, the cheeses retain high humidity and low fat content, obtaining a crumbly product, due to the modification of the casein matrix which is the one that gives rigidity to the cheeses.